IMPROVING EDUCATION AND DETERMINING THE NUTRITIONAL STATUS OF TODDLERS IN REALIZING NUTRITION-CONSCIOUS FAMILIES IN BANYUWANGI USING R-SHINY - Chamidah, Nur; Kurniawan, Ardi; Saifudin, Toha; Sa'idah, Andini; Widyawati, Ayu; Fajrina, Sofia (Universitas Airlangga, 2024)
Stunting is a condition where a child's development and growth is disturbed, which has long-term impacts, including the potential for impaired brain development due to insufficient cognitive development and a greater risk of developing chronic diseases such as diabetes, hypertension, obesity, cancer, and so on. One effort to reduce stunting rates is to increase knowledge of nutrition awareness in the family. UNAIR Statistics Study Program, participates in efforts to reduce stunting rates with community service activities (Pengmas), in the form of outreach activities regarding basic and practical knowledge in the form of workshops and training activities using R-Shiny based WEB and Android to determine the nutritional status of toddlers which can used anywhere and anytime. This community service activity was carried out in the working area of